Models of Ethical Marketing Force in Indonesian Islamic Bank - Zubair, Muhammad Kamal; Nasuka, Moh (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
This research illuminates the ethical standards governing marketing professionals within the Islamic banking sector, focusing on discouraging unethical practices for personal gain. We objectively depict the prevailing ethical landscape using field research and descriptive methodologies. Our investigation reveals that the largest Islamic Bank in Indonesia, Bank Syariah Indonesia (BSI), has instituted a comprehensive ethical framework for its marketing personnel. This framework transcends mere guidelines, embodying an ethos deeply ingrained in their professional conduct. Marketing strategies, underpinned by Islamic ethics, are guided by the tenets of faith: Shiddiq (honesty), Amanah (responsibility), Fathanah (wisdom), and Tabligh (communicative). This study offers a unique insight into the ethical marketing practices within the Islamic banking industry, contributing to the discourse on ethical standards in financial services marketing.